TOWARDS THE DIGITAL WINCHESTER: EDITING THE WINCHESTER MANUSCRIPT OF MALORY’S MORTE DARTHUR’ - Takako, Kato (International Journal of English Studies, 2009)
Seventy years since the epoch-making discovery of the Winchester manuscript, the unique manuscript of Sir Thomas Malory’s Morte Darthur, scholars have eventually recovered from the severe shock of the discovery, and have started to study the manuscript as ’a historical artefact’. The original form of the manuscript, however, is still now unwarrantedly inaccessible, considering the wealth of evidence bearing on it. In this essay, Malory scholarship before and after the discovery is ovewiewed, and a new digital edition of Winchester is proposed.